Formulasi Sediaan Gel Hand Sanitizer Ekstrak Etanol Daun Kayu Jawa (Lannea Coromendelica Houtt. Merr). - nur indah mayang safitri Suhardi (Yayasan Pendidikan Medika Indonesia, 2022)
Kayu Jawa leaves (Lannea coromendelica Houtt. Merr) contain flavonoids, saponins, tannins and polyphenols and are proven to have antibacterial effects, but their use by the community is still traditional so it needs to be developed into a formula that is more practical to use, and lasts longer, such as hand sanitizer. The purpose of this study was to determine the extract of Jawa Kayu Leaves (Lannea coromendelica Houtt. Merr) can be formulated into a hand sanitizer gel and to determine the concentration of the Jawa Kayu Jawa Leaves (Lannea coromendelica Houtt. Merr) Hand Sanitizer gel as an antiseptic. Kayu Jawa leaves (Lannea coromendelica Houtt. Merr) were extracted using maceration method using 96% ethanol solvent and made into hand sanitizer gel using carbomer 940, triethanolamine (TEA), methyl paraben, propylene glycol and aquadest. The results showed that the four preparations were homogeneous, brownish green in color and had a slightly distinctive smell with a pH range of 4.5-6.5 in the four formulations, the dispersion measurement was 5-7 cm in the four formulations, the positive control and negative control met the requirements, the gel preparation Javanese wood leaves (Lannea coromendelica Houtt. Merr) in all formulas with different base concentrations showed antiseptic effectiveness, with a 1% carbopol concentration formulation reducing the number of colonies by 14% compared to other formulations. Keywords: Gel Hand Sanitizer, Ethanol Extract of Javanese Wood Leaves (Lannea coromendelica Houtt. Merr), Physical Test, and Antiseptic Test.